The Role and Function of Education in Developing the Islamic Education Curriculum - Siti Muthiatun Najiyah; Wirdatul Hasanah; Diah Ainun Khafidloh; Nanang Budianto (Penerbit Presisi Pustaka, 2026)
The curriculum is crucial to the education system because it serves as a roadmap for creating and implementing the learning process. It comprises several elements, such as topics, instructional strategies, and assessments, that help students achieve their learning objectives. Curriculum creation must consider national education standards and be tailored to meet the needs of students, the community, and the workforce. Curriculum helps young people move toward a brighter future characterized by enhanced understanding, more developed skills, and more inclusive attitudes because it is a dynamic and responsive tool.